The real world and thinking of thyroid cancer in China. Issue 7 (December 2019) - Han, Lin; Wu, Zhen; Li, Wenlei; Li, Yingxue; Ma, Jinglin; Wu, Xinxin; Wen, Wenjuan; Li, Rui; Yao, Yumin; Wang, Yongkun
Abstract : Summary: The incidence of thyroid cancer has increased year by year, which has a major impact on the physical and mental health of patients. At the same time, it has a heavy psychological and economic burden on society and individuals. Based on the actual data of the thyroid cancer in Liaocheng People' Hospital in 2017, combine with the national and regional characteristics of China, this paper analyzes and discusses the controversy of initial thyroid operation modus. Materials and methods: The clinical and pathologic data of 552 patients of thyroid cancer were collected from the department of thyroid surgery, who were initially discovered and treated surgically. 40 patients underwent endoscopic surgery, the range of resection was lobectomy+central lymph node dissection of the affected lobe. There were 512 cases underwent open operation with total thyroidectomy+central lymph node dissection, 239 of which were treated with neck lateral lymph node dissection at the same time. Results: The overall metastasis rate of all patients was 59.42%. Even the lymph node metastasis of papillary thyroid microcarcinoma was as high as 46.92%. When the mass rose above 2 cm, the proportion of metastasis increased to 77.53%. When the tumor was complicated with bilateral and multiple high risk factor etc the proportion of metastasis were 63.54% and 71.19%, respectively. Meanwhile, the incidence of contralateral accidental malignancy was 7.25% after postoperative paraffin pathology. Conclusion: The malignant degree of thyroid cancer depends on the evolution of the tumor genome and there is a high rate of neck lymph node metastasis, especially when associated with high risk factors. It is recommended that at least total thyroidectomy+central lymph node dissection should be performed in initial treatment in China to avoid the risk of secondary operation and the burden of body and mind.